Infantile systemic hyalinosis - Report of two cases with identification of a novel gene mutation - Sandipan Dhar; Rashmi Agarwal; Sahana M Srinivas; Subhra Dhar; Apurba Ghosh (Wolters Kluwer Medknow Publications, 2022)
Infantile systemic hyalinosis (ISH; MIM #236490) and juvenile hyaline fibromatosis (MIM #228600) represent two spectrums of the rare autosomal recessive disorder, the hyaline fibromatosis syndrome caused by mutations in ANTXR2/CMG2 encoding capillary morphogenesis protein-2. Herein, we report two cases of ISH with different clinical presentations confirmed by CMG2 gene mutations. Homogenous 79 bp deletion of the entire exon 11 reported in one of the cases has not been reported previously.